2013
DOI: 10.5194/acp-13-11295-2013
|View full text |Cite
|
Sign up to set email alerts
|

Linking biogenic hydrocarbons to biogenic aerosol in the Borneo rainforest

Abstract: Abstract. Emissions of biogenic volatile organic compounds are though to contribute significantly to secondary organic aerosol formation in the tropics, but understanding these transformation processes has proved difficult, due to the complexity of the chemistry involved and very low concentrations. Aerosols from above a Southeast Asian tropical rainforest in Borneo were characterised using liquid chromatography-ion trap mass spectrometry, high-resolution aerosol mass spectrometry and Fourier transform ion cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
3
13
3
Order By: Relevance
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 66%
“…In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006). In this study, the required solid-phase extraction step precluded the detection of isoprene-derived organosulfates, which would have been removed prior to analysis.…”
Section: Biogenic Influencesupporting
confidence: 66%
“…However, some regions will be impacted by both high isoprene and DMS concentrations, for example tropical islands, such as Borneo, which can have high isoprene concentrations and are strongly influenced by marine air masses (MacKenzie et al, 2011), as well as significant terrestrial sources from vegetation and soils in the Amazon, especially into the evening and at night (Jardine et al, 2015), when ozonolysis chemistry is at its most effective relative to photochemical OH chemistry. High sulfate composition of organic aerosols collected from the Borneo rainforests likely arises from the chemical processing of oceanic emissions of DMS and SO 2 (Hamilton et al, 2013). The sulfate content of aerosols was observed to increase further over oil palm plantations in Borneo, where isoprene concentrations may reach levels on the order of tens of ppbv (MacKenzie et al, 2011), indicating scope for alkene ozonolysis-DMS chemical interactions to become significant.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
“…Studies of secondary organic aerosol (SOA) have identified a variety of nitrated organosulfate compounds (e.g., nitrooxy-organosulfates) in both chamber and ambient aerosol samples following isoprene and monoterpene oxidation. These compounds are either produced under high NO x conditions or from nighttime NO 3 radical chemistry (Surratt et al, 2006Darer et al, 2011;Lin et al, 2013a;He et al, 2014;Worton et al, 2013). Potential SOA precursors such as unsaturated green leaf volatiles (GLVs) released by wounded plants (e.g., crop harvesting and insect attacks) may contribute substantially to the budget of biogenic SOA formation, especially in remote forests Hamilton et al, 2013;Shalamzari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are either produced under high NO x conditions or from nighttime NO 3 radical chemistry (Surratt et al, 2006Darer et al, 2011;Lin et al, 2013a;He et al, 2014;Worton et al, 2013). Potential SOA precursors such as unsaturated green leaf volatiles (GLVs) released by wounded plants (e.g., crop harvesting and insect attacks) may contribute substantially to the budget of biogenic SOA formation, especially in remote forests Hamilton et al, 2013;Shalamzari et al, 2016). The detection of reaction products such as organosulfates and nitrooxy-organosulfates in ambient aerosols provides strong evidence of influence from anthropogenic sources (e.g., SO 2 and NO x ) interacting with biogenic precursors to form nitrogenated SOA Lin et al, 2013a;Meade et al, 2016).…”
Section: Introductionmentioning
confidence: 99%